1997
DOI: 10.1002/(sici)1098-1063(1997)7:3<271::aid-hipo3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

?isoform-selective changes in PKC immunoreactivity after trace eyeblink conditioning in the rabbit hippocampus

Abstract: An immunocytochemical examination of the rabbit hippocampus was done to determine which of the Ca 21 -dependent protein kinase C (PKC) isoforms (PKCa, -bI, -bII, or -g) are involved in associative learning. The hippocampally dependent trace eyeblink conditioning task was used for behavioral training, and pseudoconditioned and naive animals served as controls. Significant increases (P F 0.05) in staining intensity were found with antibodies reactive with the catalytic or the regulatory domain of PKCg in conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…Increase in membraneassociated PKC has been demonstrated in the hippocampus and cerebellum of rabbits after learning EBC (31)(32)(33). However, a decrease in membrane-associated PKC has also been shown in the hippocampus after spatial learning in rats and mice (34)(35)(36).…”
mentioning
confidence: 94%
“…Increase in membraneassociated PKC has been demonstrated in the hippocampus and cerebellum of rabbits after learning EBC (31)(32)(33). However, a decrease in membrane-associated PKC has also been shown in the hippocampus after spatial learning in rats and mice (34)(35)(36).…”
mentioning
confidence: 94%
“…The extent of spatial memory impairment among aged rats correlates negatively with levels of PKCγ in hippocampal homogenates measured by quantitative western blotting (Colombo, Wetsel, & Gallagher, 1997). Studies by Van Der Zee, Compaan, de Boer, and Luiten (1992) and Van Der Zee, Kronforst-Collins, Maizels, Hunzicker-Dunn, and Disterhoft (1997) have shown that immunoreactivity for PKCγ increases in the hippocampus following spatial learning. Additionally, activation of PKCγ by agonists prior to fear conditioning training result in significantly improved learning and increased hippocampal membrane-bound PKCγ (Smith & Wehner, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other paradigms like trace eyeblink conditioning require many more days of training (i.e., 7-14 days), and therefore have been more difficult for in vivo tracking of single neuron activity across acquisition (e.g., McEchron and Disterhoft, 1997). It may also be convenient to use the trace fear model for other types of experiments where trace eyeblink conditioning has been used in the past, e.g., examining the learning-related changes in the biophysical properties of hippocampal neurons in vitro (e.g., , and examining the learning-related changes in the biochemical properties of hippocampal neurons (e.g., Van der Zee et al, 1997). Another advantage of trace HR conditioning is that the time course of the HR index can be measured over a long 10-s trace conditioning trial.…”
mentioning
confidence: 99%